Three-Dimensional Rapid Printing–Assisted Individualized Total Nasal Reconstruction Based on a Database of Normal External Noses. Issue 4 (4th August 2022) - Wei, Hanxiao; Zhang, Aijun; Tao, Changbo; Li, Xueyang; Li, Qiang; Shen, Caiqi; Wang, Pingping; Jin, Peisheng
Abstract : Background: The nose is an unpaired facial structure. Applying three-dimensional rapid printing to total nose reconstruction is difficult because no paired structure is available for reference. In this study, three-dimensional laser scanning was used to create a database of normal external noses of Han Chinese individuals in East China to assist in total nose reconstruction. Methods: Three-dimensional laser scanning was used to create a database of normal external noses. Patients scheduled for nasal reconstruction had their measurements scaled according to head circumference and facial proportions to simulate a new reconstructed shape for the residual nose using this database. The personalized new shape was produced using rapid three-dimensional printing for preoperative evaluation and surgical design. Results: In the database of external noses, the medium nose type was the main type among Han adults in East China (64.15 percent), followed by the narrow nose type (26.34 percent). Quantitative analysis showed that blood loss and operative times were lower in the study group than in the traditional surgery group ( p < 0.05). A postoperative nasal appearance satisfaction questionnaire showed that the appearance satisfaction rate, daily life measures, and perioperative comfort were significantly better in the study group ( p < 0.05). Conclusions: The database of external noses can bridge three-dimensional printing with total nasal reconstruction. The database has important clinical significance for optimizing the shape of the nose, reducing intraoperative blood loss, shortening the operative time, and improving patient satisfaction. This study provides new insight for the application of computer-guided three-dimensional scanning and rapid printing in organ reconstruction.